Aporte político de Matilde Hidalgo a los procesos de democratización en el Ecuador - Duchi Achance, Alexis Jair (2022)
This research arises from the need to identify the contribution of a famous woman named Matilde Hidalgo de Procel who fought for equal rights in favor of women and their participation in Ecuadorian politics: Taking as a starting point her primary and secondary studies which determined her future and the breakdown of a conservative model of the time in which women had neither voice nor vote. She was the pioneer in the educational, political, social field and establishing and at the same time she was the First Bachelor of Loja, the first graduate in medicine, the first doctor of Ecuador, but one of the most important and recognized achievements at the level of Ecuador and Latin America was The Right to Vote for Women, being an example of struggle, tenacity and improvement in every field in which she developed. Within the bibliographic exploration, information was collected in books, articles and other publications that refer exclusively to men as collective and individual protagonists of history. Jenny Estrada, a prominent Ecuadorian writer, historian and feminist, makes a biographical narrative of the invisible lady and highlights the limitation of women's rights in the 20th century. It also evidences the fruits of the epic brawl that she maintained through time and the empowerment of her rights being currently a fundamental part of the Ecuadorian state that involves girls, women, mothers, wives and workers, etc.